LEGAL NATURE OF THE UNDERWRITING COMMITMENT CONTRACT IN THE CAPITAL MARKET - Ali Ansari; seyed mortaza shahidi; hassan azarniyush (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2019)
In accordance with the definition of Article 1 of the Securities Market Act, a commitment is a third party's commitment to purchase securities that have not been sold within the deadline. The publisher intends to transfer the various risks involved in the filing process to a trusted one. In this way, the underwriting contract is the role of insurance finance in the supply of securities. Given the existing methods in the capital markets of different countries to conclude an accrual contract, this contract can have a different legal nature. In selected capital markets, the obligee accepts the acquisition of securities, while in the capital market of Iran, the ownership of the securities is not transferred to the obligated issuer. By concluding the contract, the publisher will be obliged to enter into a secondary contract. Subject to the obligation contained in this contract, the intention of the parties in the form of a contract cannot be accepted. Unlike the current method in the capital market in the selected countries, this type of commitment creates a personal relationship and covenant between the parties and there is no transfer of ownership involved.